Enhancement of Thulium–Ytterbium doped fiber laser efficiency using dual‐pumping method. Issue 2 (February 2015) - Saidin, N.; Harun, S. W.; Ahmad, H.; Ali, S. M. M.; Damanhuri, S. S. A.; Halder, A.; Paul, M. C.; Das, S.; Pal, M.; Bhadra, S. K.
ABSTRACT Performance enhancement of laser acquired from a newly developed double‐clad Yb3+/Tm3+ codoped fiber (YTDF) is demonstrated using dual‐pumping scheme. The laser uses a 2 m long YTDF fiber with a core dopant concentrations (in wt%) of 2.00 Yb2O3, 0.5 Tm2O3, 1.0 Al2O3, and 3.00 Y2O3 as a gain medium in conjunction with a pair of fiber Bragg grating in a linear cavity resonator to generate lasing at 1901.6 nm. The best efficiency of 2.9% and the highest output power of 27 mW are obtained by combining 927 nm pump with 905 nm pump. As compared to a single pumping scheme using 927 nm pumping source, about 0.43% increment in efficiency is observed with no evidence of rollover at the highest output power. The best combination is to use 200 mW of 800 nm pump with 927 nm pump, wherein only a total pump power of 1900 mW is required to generate 20 mW of 1.9 μm laser output. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:285–287, 2015